Establishment of Novosibirsk Academgorodok – Centre of the Siberian Branch of the Russian Academy of Sciences: Achievements and Omissions - A. G. Aganbegyan (Ekonomika Nauki)
This paper, written to commemorate the anniversary of the Russian Academy of Sciences, offers a detailed account of the establishment of Novosibirsk Akademgorodok. The author, Academician Abel Gezevich Aganbegyan, played an active role in this process. He regards Akademgorodok as a major contributor to the advancement  of science and education. Akademgorodok was initially created to accomplish three primary objectives: to foster the development of fundamental sciences and facilitate their mutual interaction, with a focus on breakthrough directions; to integrate science with higher and pre-university education; and to promote innovation based on scientific achievements. These goals demanded significant efforts from both the research community and the state. Despite significant challenges and risks, Akademgorodok has become one of the leading scientific centres both in Russia and globally. However, this process was associated with some omissions, including insufficient attention to the commercialisation of scientific findings and innovation transfer in industry.